2007
DOI: 10.1007/s00421-007-0640-3
|View full text |Cite
|
Sign up to set email alerts
|

Similar cardiac vagal withdrawal at the onset of arm and leg dynamic exercise

Abstract: Electrocardiogram RR intervals duration reduce rapidly in the first seconds of dynamic exercise mainly due to a cardiac vagal withdrawal. However, it remains unclear if this response varies between exercises performed with different body segments (i.e. arm vs. leg). Our aim was to compare the vagal withdrawal at the onset of arm and leg dynamic exercise. Cardiac vagal withdrawal was assessed by the 4-s exercise test (4sET), a pharmacologically validated and highly reliable procedure. Initially, 60 healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
7
1
1
Order By: Relevance
“…This aspect is clinically interesting, as previous studies with the latter protocol have demonstrated that the rapid movement of the legs or arms 39 and even the bending of wrists 40 is capable of inducing a rapid and sharp increase in heart rate and also the SBP 41 and that this response can be completely abolished by selective pharmacological blockade with atropine 42 , characterizing the mechanism of vagal inactivation as responsible for the response.…”
Section: Discussionmentioning
confidence: 91%
“…This aspect is clinically interesting, as previous studies with the latter protocol have demonstrated that the rapid movement of the legs or arms 39 and even the bending of wrists 40 is capable of inducing a rapid and sharp increase in heart rate and also the SBP 41 and that this response can be completely abolished by selective pharmacological blockade with atropine 42 , characterizing the mechanism of vagal inactivation as responsible for the response.…”
Section: Discussionmentioning
confidence: 91%
“…Tulppo et al (1999) reported a faster vagal withdrawal during dynamic incremental exercise performed with the arms than the legs, while Muraki et al (2004) found similar vagal withdrawal comparing arm and leg dynamic steady state exercises at low and high intensities. More specifically, considering the immediate transition from rest to exercise, Silva et al (2008) reported that similar cardiac vagal withdrawal was induced by 4-s fast unloaded cycling exercise performed with arms or legs. However, a general limitation of the studies was that the confounding effects of central command and muscle metaboreflex were not controlled.…”
Section: Discussionmentioning
confidence: 97%
“…1 Diagram of the custom-built apparatus designed to allow simultaneous arm and leg passive movements with both arms (2 limbs); (3) passive exercise with both arms combined with one leg (3 limbs); (4) passive exercise with both arms and both legs (4 limbs). The passive exercise bouts were performed against no resistance (unloaded cycling) from the 4th to the 8th second of a 12-s apnea at individual total lung capacity (Araújo et al 1992;Nóbrega and Araújo 1993;Silva et al 2008;Vianna et al 2008). Passive movement was carried out by the experimenter manually cycling the subject's limbs at *60 rpm.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The physiological mechanisms involved in 4sET are different from the mechanisms involved in HRV and RSA. In 4sET , there is a rapid withdrawal of cardiac vagal modulation at rest due to a redundant interaction between nerve impulses that converge in the brainstem from motor centers in the brain 24,25 and from afferent nerve fibers (mainly type III -mechanoreflex) coming from the skeletal muscles 26,27 . Thus, the central and peripheral mechanisms inhibit cardiac vagal modulation, promoting an increase in heart rate.…”
Section: Figure 1 -Comparison Of Cardiac Vagal Modulation Assessed Bymentioning
confidence: 99%